Development and Evaluation of Orthographic Knowledge Awareness Scale for Children Aged 6–12 Years - Yachun Xie; Yachun Xie; Qu Xu; Liying Liu; Mengmeng Yao; Panting Liu; Meiling Tong; Qin Hong; Xia Chi; Xia Chi (Frontiers in Psychology, 2022)
ObjectiveThis study primarily aimed to develop an orthographic knowledge awareness scale in Mandarin for children aged 6–12 years. Related factors affecting orthographic knowledge awareness in children were analyzed, and a basis for individualized intervention was provided to improve reading and writing.MethodsA conceptual framework for orthographic knowledge awareness in children aged 6–12 years was determined through a detailed reading of the literature on Chinese character orthography, combined with qualitative interviews of the target population and consultation with experts. The orthographic knowledge awareness scale initially consisted of three versions: for grades 1–2 (210 items), grades 3–4 (207 items), and grades 5–6 (220 items), accumulating a total of 637 items. The initial scale was then used for the study involving children aged 6–12 years in Maanshan City, Jiangsu Province. Various approaches to screening items were comprehensively used to determine the formal version of the orthographic knowledge awareness scale. The official scale was ultimately used to conduct the third round of surveys among 1,354 children aged 6–12 years in ordinary primary schools located in 5 cities in Jiangsu Province, namely, Changzhou, Lianyungang, Nantong, Xuzhou, and Yangzhou. The reliability, validity, and discriminating power of the formal scale were evaluated.ResultsA total of 360 items were included in the formal version of the orthographic knowledge awareness scale. The formal scale was divided into three versions for grades 1–2, 3–4, and 5–6. Each grade version consisted of 120 items. The scale was composed of the stroke awareness test, radical awareness test, and left–right reversal test. The cumulative variance contribution rates of grades 1–2, 3–4, and 5–6 were 82.47, 61.71, and 64.19%, respectively. The Cronbach's α coefficients of the three-grade version of the scale were 0.989, 0.946, and 0.938; the split-half reliability coefficients were 0.925, 0.766, and 0.847; and the test–retest reliability coefficients were 0.847, 0.895, and 0.8928, respectively.ConclusionThe proposed orthographic knowledge awareness scale for children aged 6–12 years exhibits good reliability and validity. The formal scale consisted of two dimensions: identification of left–right reversal at the stroke and radical levels and the left–right reversal at the whole character level. The two dimensions can more comprehensively reflect the ability of children to discriminate orthographic structures.